Answer: The simplification is [tex]5*a^{-9}*b^{-9}[/tex]
Step-by-step explanation:
Here we need to use the property:
[tex]\frac{a^n}{a^m} = a^{n - m}[/tex]
We have the expression:
[tex]\frac{25*a^{-5}*b^{-8}}{5*a^{4}*b}[/tex]
We can separate it in parts with the same base, then we can rewrite this as:
[tex]\frac{25*a^{-5}*b^{-8}}{5*a^{4}*b} = \frac{25}{5} \frac{a^{-5}}{a^4} \frac{b^{-8}}{b}[/tex]
Using the first property we can rewrite this as:
[tex]\frac{25}{5} \frac{a^{-5}}{a^4} \frac{b^{-8}}{b} = 5*a^{-5 - 4}*b^{-8 - 1} = 5*a^{-9}*b^{-9}[/tex]